ANALISIS PROGRAM BERAS DAERAH (RASDA) GUNA MEWUJUDKAN KESEJAHTERAAN RUMAH TANGGA SASARAN PENERIMA MANFAAT (RTS-PM) DI KABUPATEN MALINAU PROVINSI KALIMANTAN UTARA - Tria Hilda; Hadi Prabowo; Ika Sartika (Jurnal Kebijakan Pemerintahan, 2022)
Abstract The Regional Rice Program (RASDA) is one of the flagship programs of the Regional Government of Malinau Regency, in Realizing Household Welfare Target Beneficiaries. The purpose of this study was to find out how the Analysis of the Regional Rice Program (RASDA) to embody the welfare of the targeted households of beneficiary (RTS-PM) in Malinau Regency, North Kalimantan Province and to find out the barriers of Malinau Regency Government in implementing the RASDA program. This research is an analytical descriptive study, which is a description that describes and examines problems based on the government policies through adequate government regulations. This study uses a qualitative descriptive research method using a conceptual approach, where the source of the data is obtained through library research with reference to David’s Management theory (2011) namely a) Planning b) Organizing; c) Motivating; d) Placement of Staff; and e) Controlling. Thus, this study examines and compares the contents of the regional sovereignty legislation related to food and local regulations governing regional rice (RASDA) which is one of the flagship programs of the Malinau Regency Government. The results of the analysis of the Regional Rice Program (RASDA) to comprehend the welfare of the targeted households of beneficiary households (RTS-PM) in Malinau Regency, North Kalimantan Province have been going statisfactorily. This can be recognized from four aspects, namely: (1) Aspects of Government Policy; (2) Aspects of Fulfillment of RTS-PM Rights; (3) Management Aspects of Regional Rice (RASDA) Distribution; (4) Quality Aspects of Regional Rice (RASDA). Keywords: Regional Rice Program (RASDA), Wellbeing, Target Beneficiary Households (RTS-PM).